E-MODUL KURIKULUM MERDEKA BERBASIS PROJECT BASED LEARNING (PjBL) BERMUATAN KARAKTER PADA SISWA SMP SEDERAJAT - Putri Nabila; Utin Desy Susiaty; Muhamad Firdaus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce an independent curriculum e-module based on project-based learning with character in parallelogram materials that can achieve a level of validity, practicality, and effectiveness. This research is a type of Research and Development (R&D) research using the ADDIE development model. The instruments used to collect data are expert validation sheets, teacher response questionnaires, student response questionnaires, and post tests. Based on the results of the first study, material validation and media validation with an overall average score of 91.92% with very valid criteria. Second, the practicality value is seen from the teacher response questionnaire and the student response questionnaire with an overall average score of 89.58% which shows very practical criteria. As for the third, the effectiveness of the media developed was obtained from the results of the student's post test. For the results of class completeness (%)≥70, a score of 65.39% was obtained so that the level of effectiveness of the e-module was effective.